Gel polymer electrolyte based on sulfuryl electrolyte and preparation method and application thereof
By using in-situ polymerization technology in lithium-ion batteries, the gel polymer electrolyte based on sulfone-based electrolytes are solved, and the demand for high-performance lithium-ion batteries is achieved.
Patent Information
- Application Number
- CN202411941819.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-02-28
AI Technical Summary
The existing gel polymer electrolytes have shortcomings in ionic conductivity and interface compatibility, and it is difficult to meet the needs of high-performance lithium-ion batteries.
Using in-situ polymerization technology, lithium salt is mixed with sulfone-based organic solvent, weak solvated solvents and monomers, and free radical initiators are added to form a gel polymer electrolyte based on sulfone-based electrolyte.
It improves the ionic conductivity and interface compatibility of the electrolyte, reduces the interface impedance, improves the rate performance and cycle stability of the battery, and enhances the safety and stability of the battery.
Smart Images

Figure CN119542526A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a gel polymer electrolyte based on a sulfone-based electrolyte, and a preparation method and application thereof. Background Art
[0002] As the global demand for energy continues to rise, electric vehicles and renewable energy storage technologies are becoming increasingly important. Although lithium metal anodes were once ignored due to safety concerns caused by dendrite problems, researchers have regained interest in them due to their low potential (-3.04V relative to standard hydrogen electrode) and high specific capacity (3860mAh / g). The formulation of the electrolyte is crucial to the performance, cycle life and safety of the battery, and has therefore become a research focus. Traditional carbonate electrolytes have shortcomings in high voltage and thermal stability, which requires the development of new, non-flammable electrolytes that are compatible with lithium metal anodes and high-voltage cathodes. To address these issues, researchers have begun to turn their attention to solid and gel electrolytes. Gel polymer electrolytes (GPEs), as an electrolyte between solid and liquid, have good flexibility, mechanical strength, ionic conductivity and high safety, and are considered to be an ideal choice to replace traditional liquid electrolytes. However, most of the existing gel polymer electrolytes are based on carbonate solvents, which are easily decomposed at high temperatures and have a narrow electrochemical window, making it difficult to meet the needs of high-performance lithium-ion batteries.
[0003] Sulfone compounds, as a high-performance solvent, are increasingly attracting researchers' attention for their potential applications in the field of electrochemistry. This compound has a series of remarkable properties, including a high electrochemical stability window, which means that it can remain stable over a wide voltage range and is not prone to decomposition, thereby improving the safety and stability of the battery. At the same time, sulfone compounds exhibit good ionic conductivity, which is crucial for electrolytes because it can effectively improve the charge and discharge efficiency and overall performance of the battery. In addition, the flame retardancy of sulfone compounds is also a highlight, which to a certain extent reduces the risk of fire in batteries under extreme conditions.
[0004] Based on these excellent properties of sulfone compounds, researchers have begun to turn their attention to the study of gel polymer electrolytes based on sulfone-based electrolytes. As a material between traditional liquid electrolytes and all-solid-state electrolytes, gel polymer electrolytes combine the ionic conductivity of liquid electrolytes with the safety and mechanical properties of solid electrolytes. Therefore, combining sulfone-based electrolytes with gel polymer electrolytes is expected to develop electrolyte materials that are both safe and efficient.
[0005] However, despite the broad prospects, the current research on gel polymer electrolytes for sulfone-based electrolytes is still in its infancy. In the actual research and development process, researchers have encountered some challenges and problems. First, the existing sulfone-based gel polymer electrolytes are insufficient in ionic conductivity, which may be due to the weak interaction between the polymer matrix and the sulfone-based electrolyte, resulting in low ion transfer efficiency. Secondly, poor interface compatibility is another problem that needs to be solved urgently. The poor interface compatibility between the gel polymer electrolyte and the electrode material will lead to increased interfacial impedance, affecting the cycle stability and rate performance of the battery. In addition, how to further improve the ionic conductivity and mechanical properties of the electrolyte while maintaining the flame retardancy of the sulfone-based compounds is also a technical problem that researchers need to overcome.
[0006] Therefore, to overcome the existing challenges, researchers are seeking to develop a new type of gel polymer electrolyte, which should be easy to prepare, have low resistance, good wettability, high ionic conductivity, high oxidation potential (to accommodate high-voltage cathodes), and compatibility with sulfone-based electrolyte systems. Summary of the invention
[0007] In view of the deficiencies of the prior art, the present invention provides a gel polymer electrolyte based on a sulfone-based electrolyte, a preparation method thereof, and an application of the gel polymer electrolyte in a battery.
[0008] The present invention adopts the following technical solution:
[0009] A method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte comprises the following steps:
[0010] S1, mixing a lithium salt with a sulfone-based organic solvent, and then adding a weak solvating solvent to the mixture of the lithium salt and the sulfone-based organic solvent to obtain a basic electrolyte, i.e., a sulfone-based flame-retardant electrolyte;
[0011] S2, dissolving the monomer and the free radical initiator in the basic electrolyte obtained in step S1 according to a preset ratio to form a precursor solution;
[0012] S3. Assemble the precursor solution in a battery and heat it at 60-80° C. for 4-24 hours to obtain a gel polymer electrolyte.
[0013] The lithium salt in the basic electrolyte in step S1 is one or more of lithium bis(trifluoromethanesulfonyl)imide (referred to as LiTFSI), lithium bis(fluorosulfonyl)imide (referred to as LiFSI), lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate, lithium tetrafluoroborate, lithium difluorooxalatoborate (referred to as LiDFOB), lithium dioxalatoborate, and lithium trifluoromethanesulfonate.
[0014] The sulfone-based organic solvent in the basic electrolyte in step S1 is one or more of dimethyl sulfone (abbreviated as: DMS), dimethyl sulfoxide (abbreviated as: DMSO), ethyl methyl sulfone (abbreviated as: EMS), 3-methylcyclopentane (abbreviated as: MSL) and cyclopentane (abbreviated as: SL).
[0015] The weak solvating solvent added in step S1 is one or more of bromobenzene, hexafluorobenzene, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether (abbreviated as: HFE), bis(2,2,2-trifluoroethyl) ether (abbreviated as: BTFE), methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (abbreviated as: TTE), hexafluorocyclotriphosphazene, ethoxy(pentafluoro)cyclotriphosphazene, and methyl trifluoroethyl carbonate (abbreviated as: FEMC).
[0016] The volume ratio of the sulfone-based organic solvent to the weak solvating solvent added in step S1 is 2:1-1:4; the concentration of the lithium salt in the basic electrolyte is 1-3 mol / L.
[0017] The monomer added in step S2 is one or more of N,N'-methylenebisacrylamide (MBA), methyl methacrylate (MMA), ethoxylated trimethylolpropane triacrylate (ETPTA), pentaerythritol tetraacrylate (PETEA), polyethylene glycol dimethacrylate (PEGDMA), butyl hexafluoroacrylate (HFBA), isopropenyl diethyl phosphate, and vinyl diethyl phosphate.
[0018] The free radical initiator added in step S2 is one of azobisisobutyronitrile (abbreviated as AIBN), cyclohexanone peroxide, azobisisoheptanenitrile, tert-butyl hydroperoxide, and dimethyl azobisisobutyrate.
[0019] The mass ratio of the monomer, the free radical initiator and the basic electrolyte added in step S2 is (1%-10%): (0.1%-0.5%): (89.5%-98.9%).
[0020] A gel polymer electrolyte based on a sulfone-based electrolyte obtained according to the preparation method.
[0021] An application of a sulfone-based electrolyte gel polymer electrolyte obtained according to the above preparation method in a battery, the battery comprising a high-voltage positive electrode, a negative electrode, a separator and the above gel polymer electrolyte; the high-voltage positive electrode is NCM811, and the negative electrode is one or more of lithium metal, graphite, and mesophase carbon microspheres.
[0022] The technical solution of the present invention has the following advantages:
[0023] A. The present invention utilizes in-situ polymerization technology to allow the polymer skeleton and sulfone-based electrolyte to be mixed more evenly, thereby improving the ionic conductivity and interfacial compatibility of the electrolyte, effectively reducing the interfacial impedance between the gel polymer electrolyte and the electrode material, and improving the rate performance and cycle stability of the battery. Due to the contribution of the weak solvating solvent, the electrolyte presents a solvation structure dominated by anions, and the generated inorganic-rich interface layer is conducive to stabilizing the phase change of the high-voltage positive electrode, while inhibiting the growth of metal lithium dendrites or the co-intercalation behavior of the graphite negative electrode. The use of high-polarity, high-thermal stability sulfone-based solvents helps to achieve both good electrical performance and safety in the battery system.
[0024] B. The electrolyte system designed in the present invention achieves high performance in high-voltage NCM811||Li batteries, and exhibits excellent cycling performance in assembled Li||Li symmetric batteries, highlighting its good compatibility with lithium metal and its ability to inhibit the growth of lithium dendrites.
[0025] C. The present invention constructs a unique anion-rich solvation structure, which helps to form a stable solid electrolyte interface film (SEI), thereby improving the cycle stability and life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the specific embodiments of the present invention, the drawings required for use in the specific embodiments will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0027] Figure 1 The in-situ polymerization mechanism is initiated by free radicals;
[0028] Figure 2 Cycling performance diagram of Li-Li symmetric cells assembled with different sulfone-based electrolytes;
[0029] Figure 3 Cycling performance diagram of Li-NCM811 batteries assembled with different gel polymer electrolytes;
[0030] Figure 4 EIS graph of Li-NCM811 battery assembled with sulfone-based electrolyte and gel polymer electrolyte;
[0031] Figure 5 This is a cycling performance diagram of a Li-NCM811 battery assembled using the sulfone-based gel polymer electrolyte prepared in Example 7. DETAILED DESCRIPTION
[0032] The technical solution of the present invention will be described clearly and completely below in conjunction with the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] Example 1
[0034] This embodiment provides a method for preparing a sulfone-based electrolyte, comprising the following steps:
[0035] First, SL and FEMC are mixed in a volume ratio of 1:4 to obtain a mixed solvent, and then 1M LiTFSI is dissolved in the mixed solvent, and stirred to prepare a homogeneous basic electrolyte, which is the sulfone-based electrolyte.
[0036] Example 2
[0037] The difference from Example 1 is that SL and FEMC are mixed in a volume ratio of 1:1, and other substances, amounts and preparation methods are the same as those in Example 1.
[0038] Example 3
[0039] The difference from Example 1 is that SL and FEMC are mixed in a volume ratio of 2:1, and other substances, amounts and preparation methods are the same as those in Example 1.
[0040] Example 4
[0041] This embodiment provides a method for preparing a sulfone-based electrolyte, comprising the following steps:
[0042] SL and FEMC were mixed in a volume ratio of 1:3, and then 1M LiTFSI and 0.5M LiDFOB were dissolved in the mixed solvent, and stirred to form a homogeneous basic electrolyte, which is the sulfone-based electrolyte.
[0043] Example 5
[0044] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0045] S1. Add 1.5 wt% of PETEA, 1.5 wt% of HFBA, and 0.1 wt% of AIBN to the basic electrolyte of Example 4 to obtain a precursor solution;
[0046] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 60°C for 4 hours to obtain a gel polymer electrolyte.
[0047] Example 6
[0048] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0049] S1. Add 4 wt % of N,N'-methylenebisacrylamide and 0.3 wt % of AIBN to the basic electrolyte of Example 1 to obtain a precursor solution;
[0050] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 80°C for 24 hours to obtain a gel polymer electrolyte.
[0051] Example 7
[0052] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0053] S1. Add 1 wt% of PETEA and 0.1 wt% of AIBN to the electrolyte of Example 1 to obtain a precursor solution;
[0054] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 70°C for 12 hours to obtain a gel polymer electrolyte.
[0055] Example 8
[0056] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0057] S1. Add 3wt% of PETEA, 3wt% of HFBA, and 0.2wt% of AIBN to the basic electrolyte of Example 1 to obtain a precursor solution;
[0058] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 60°C for 4 hours to obtain a gel polymer electrolyte.
[0059] Example 9
[0060] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0061] S1. Add 5 wt% of N,N'-methylenebisacrylamide (MBA), 5 wt% of ethoxylated trimethylolpropane triacrylate and 0.5 wt% of AIBN to the base electrolyte of Example 1 to obtain a precursor solution;
[0062] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 65°C for 8 hours to obtain a gel polymer electrolyte.
[0063] Comparative Example 1
[0064] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0065] S1. Add 2 wt% of N,N'-methylenebisacrylamide and 0.1 wt% of AIBN to the basic electrolyte of Example 4 to obtain a precursor solution;
[0066] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 60°C for 4 hours to obtain a gel polymer electrolyte.
[0067] Comparative Example 2
[0068] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0069] S1. Add 1 wt% of PETEA and 0.1 wt% of AIBN to the basic electrolyte of Example 4 to obtain a precursor solution;
[0070] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 70°C for 12 hours to obtain a gel polymer electrolyte.
[0071] Comparative Example 3
[0072] This embodiment provides a method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, comprising the following steps:
[0073] S1. Add 5 wt% of N,N'-methylenebisacrylamide (MBA), 5 wt% of ethoxylated trimethylolpropane triacrylate and 0.5 wt% of AIBN to the base electrolyte of Example 4 to obtain a precursor solution;
[0074] S2. Assemble the precursor solution into a battery, and then heat it in an oven at 60°C for 4 hours to obtain a gel polymer electrolyte.
[0075] Comparative Example 4
[0076] 5 wt% of N,N'-methylenebisacrylamide (MBA), 5 wt% of ethoxylated trimethylolpropane triacrylate and 0.5 wt% of AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution. The precursor solution was assembled into a battery and then heated in an oven at 60°C for 4 hours to obtain a comparative gel polymer electrolyte.
[0077] Comparative Example 5
[0078] 1 wt% PETEA and 0.1 wt% AIBN were added to a commercial electrolyte (1 M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution. The precursor solution was assembled into a battery and then heated in an oven at 70°C for 12 hours to obtain a comparative gel polymer electrolyte.
[0079] Comparative Example 6
[0080] 1.5wt% PETEA, 1.5wt% HFBA and 0.1wt% AIBN were added to a commercial electrolyte (1M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) to obtain a precursor solution. The precursor solution was assembled into a battery and then heated in an oven at 60°C for 4 hours to obtain a comparative gel polymer electrolyte.
[0081] Comparative Example 7
[0082] A commercial electrolyte (1M LiPF6 dissolved in EC and DEC in a volume ratio of 1:1, 5% FEC) was added to lithium nickel cobalt manganese oxide 811 (LiNi 0.8 Mn 0.1 Co 0.1 O2) as the positive electrode, lithium metal as the negative electrode, and polypropylene film as the separator.
[0083] Battery construction:
[0084] Positive electrode preparation: The positive electrode material LiNi0.8Co0.1Co0.1O2 (NCM811), the binder polyvinylidene fluoride (PVDF), the conductive agent acetylene black and N-methylpyrrolidone (NMP) were mixed evenly and stirred for 12 hours. The mass ratio of positive electrode material, PVDF and acetylene black was 9:0.5:0.5 to obtain positive electrode slurry. The obtained slurry was coated on the surface of aluminum foil, and then the electrode was dried in a vacuum oven (80°C, 12h). After drying, the positive electrode was cut into discs with a punching machine and placed in an argon atmosphere glove box for standby use.
[0085] Button cell construction: stack the negative electrode shell, negative electrode, and separator in the center in sequence, then add 70ul of the corresponding electrolyte, and after it moistens the separator, stack the NCM811 positive electrode, gasket, spring, and positive electrode shell in the center in sequence, and finally place the whole into the battery sealing machine for compaction, and let it stand for 24 hours before use.
[0086] Figure 1 The polymerization mechanism is free radical-initiated in-situ polymerization. The polymerization mechanism is that the free radical R· generated by the decomposition of the initiator AIBN breaks the C=C of the polymer monomer, resulting in free radical polymerization cross-linking to obtain a polymer skeleton.
[0087] Figure 2Figure 2 Cycling performance of Li-Li symmetric cells assembled for different electrolytes. -2 It can be seen that the overpotential of the symmetrical battery of commercial liquid electrolyte comparative example 7 is as low as 400mV by cycling at a current density of , but due to the serious side reactions at the interface, the overpotential significantly increases to an extremely high value after 250h, indicating that the interface between metal lithium and the electrolyte is unstable. This is mainly due to the continuous thickening of SEI and the continuous growth of lithium dendrites. The symmetrical batteries assembled with gel electrolyte can cycle for more than 400h and maintain a small overpotential. This shows that the restriction of anions by the stable polymer skeleton avoids the formation of space charge regions at the lithium negative electrode interface, reduces the side reactions caused by anions, forms a stable SEI during the cycle, and achieves excellent long-cycle performance of the symmetrical battery.
[0088] Figure 3 The cycle performance diagram of Li-NCM811 battery assembled with different gel polymer electrolytes, with a voltage range of 2.8-4.3V, shows that at 0.5C rate, after 122 cycles, the effect of Example 5 is very good. In comparison, the battery specific capacity measured in Example 5 remains stable, with a capacity retention rate of 87%, while Comparative Examples 1 and 2 have a certain attenuation, which also shows that the in-situ copolymerization of HFBA and PETEA can form stable CEI and SEI, optimize the uniform distribution of Li+ and reduce parasitic reactions, thereby showing better cycle performance.
[0089] Figure 4 It is the EIS diagram of the Li-NCM811 battery assembled with sulfone-based electrolyte and gel polymer electrolyte. The interfacial charge transfer impedance of the battery in Example 5 is 40Ω obtained by impedance simulation, which may be attributed to the improved solid electrolyte interface produced after in-situ polymerization, which reduces the contact resistance and promotes the transport of Li+. In contrast, the interfacial resistance of the batteries in Comparative Examples 6 and 7 is greater than that in Example 7. Therefore, it is shown that the introduction of the gel skeleton forms a stable interface, which may help to alleviate side reactions and promote the transport of ions.
[0090] Figure 5 The cycle performance diagram of the Li-NCM811 battery assembled with the sulfone-based gel polymer electrolyte prepared in Example 5 is shown in the voltage range of 2.8-4.3 V. The figure shows that the average capacities at current densities of 0.1, 0.2, 0.5, 1, and 2 C are 199.5, 195, 178.9, 152.5, and 100.5 mAh g, respectively. -1 When the current density returned to 0.5C, the average discharge capacity recovered to 179.6 mAh g -1 , indicating that the material has excellent stability even after undergoing rapid charge and discharge.
[0091] The present invention provides a gel polymer electrolyte based on a sulfone-based electrolyte. By optimizing the composition of a polymer skeleton and a sulfone-based electrolyte, a gel polymer electrolyte with good electrochemical stability and excellent interfacial compatibility is prepared to meet the needs of high-performance lithium-ion batteries. The sulfone-based electrolyte with good thermal stability is mixed with a polymer skeleton and the gel polymer electrolyte is prepared by in-situ polymerization, which not only reduces the interfacial resistance, but also constructs a unique anion-rich solvation structure, which exhibits excellent performance in stabilizing the nickel-rich positive electrode interface and inhibiting the growth of lithium dendrites.
[0092] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. However, the obvious changes or modifications derived therefrom are still within the scope of protection of the present invention.
Claims
1. A method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte, characterized in that: The steps include: S1, mixing a lithium salt with a sulfone-based organic solvent, and then adding a weak solvating solvent to the mixture of the lithium salt and the sulfone-based organic solvent to obtain a basic electrolyte, i.e., a sulfone-based flame-retardant electrolyte; S2, dissolving the monomer and the free radical initiator in the basic electrolyte obtained in step S1 according to a preset ratio to form a precursor solution; S3. Assemble the precursor solution in a battery and heat it at 60-80° C. for 4-24 hours to obtain a gel polymer electrolyte.
2. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The lithium salt in the basic electrolyte in step S1 is one or more of lithium bis(trifluoromethanesulfonyl imide), lithium bis(fluorosulfonyl imide), lithium hexafluorophosphate, lithium difluorophosphate, lithium nitrate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium dioxalatoborate, and lithium trifluoromethanesulfonate.
3. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The sulfone-based organic solvent in the basic electrolyte in step S1 is one or more of dimethyl sulfone, dimethyl sulfoxide, ethyl methyl sulfone, 3-methylcyclopentane and cyclopentane.
4. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The weak solvating solvent added in step S1 is one or more of bromobenzene, hexafluorobenzene, 2,2,2-trifluoroethyl-1,1,2,2-tetrafluoroethyl ether, bis(2,2,2-trifluoroethyl) ether, methyl nonafluorobutyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, hexafluorocyclotriphosphazene, ethoxy(pentafluoro)cyclotriphosphazene, and methyl trifluoroethyl carbonate.
5. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The volume ratio of the sulfone-based organic solvent to the weak solvating solvent added in step S1 is 2:1-1:4; the concentration of the lithium salt in the basic electrolyte is 1-3 mol / L.
6. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The monomer added in step S2 is one or more of N,N'-methylenebisacrylamide, methyl methacrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, polyethylene glycol dimethacrylate, butyl hexafluoroacrylate, isopropenyl diethyl phosphate, and vinyl diethyl phosphate.
7. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The free radical initiator added in step S2 is one of azobisisobutyronitrile, cyclohexanone peroxide, azobisisoheptanenitrile, tert-butyl hydroperoxide, and dimethyl azobisisobutyrate.
8. The method for preparing a gel polymer electrolyte based on a sulfone-based electrolyte according to claim 1, characterized in that: The mass ratio of the monomer, the free radical initiator and the basic electrolyte added in step S2 is (1%-10%): (0.1%-0.5%): (89.5%-98.9%).
9. A gel polymer electrolyte based on a sulfone-based electrolyte obtained by the preparation method according to any one of claims 1 to 8.
10. Use of a gel polymer electrolyte based on a sulfone-based electrolyte obtained by the preparation method according to any one of claims 1 to 8 in a battery, characterized in that: The battery comprises a high-voltage positive electrode, a negative electrode, a separator and a gel polymer electrolyte; the high-voltage positive electrode is NCM811, and the negative electrode is one or more of lithium metal, graphite and mesophase carbon microspheres.
Citation Information
Cited By
Silane coupling agent modified Mxene-based solid-state polymer electrolyte, solid-state lithium battery and preparation method of solid-state lithium battery
CN120999107A